Application of MASP for labor appropriation for railway equipment maintenance work orders - Costa, Licia Lopes Gonçalves; Souza, Neuber Samy Ferreira de; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2024)
The study aims to address the importance of maintenance management for the competitiveness of organizations, emphasizing the pursuit of efficiency in processes. In this way, the need for management strategies will be analyzed, mentioning tools such as the Methodology of Analysis and Problem Solving (MASP) and Enterprise Resource Planning (ERP) Systems, such as SAP, to enhance the effectiveness of maintenance processes. In this context, with the intention of improving the Planning and Maintenance Control (PCM) sector in a mining and logistics company, the study proposes the application of MASP to enhance labor appropriation in railway equipment work orders. Its objectives include identifying problems, applying MASP to improve the labor appropriation process, and proposing actions to minimize impacts on maintenance indicators. Tools such as MASP and PDCA are explored as methods to identify, analyze, and solve problems, ensuring continuous improvements in processes. Various MASP tools are presented, such as Pareto Chart, 5 Whys, 5W1H, Ishikawa Diagram, and Brainstorming. Thus, the application of these tools contributed to the understanding and improvement of railway maintenance management, seeking to determine the root cause and solve specific problems, and achieve continuous improvements in the labor appropriation process of railway equipment maintenance.